Method for preparing C.I. Reactive blue 49 color base through electrolysis
1-amino-4-chloroanthraquinone-2-sulfonic acid is generated by electrolytic preparation method and condensed with M acid in an autoclave, solving the problems of stannous chloride contamination and by-product of bromine in the prior art. A green and efficient preparation of C.I. active blue 49 color group was achieved.
Patent Information
- Application Number
- CN202411343884.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-25
AI Technical Summary
In the existing C.I. active blue 49 color group preparation method, the use of stannous chloride causes environmental pollution, and a reducing agent is required to maintain the monovalent copper state of the catalyst, resulting in an increase in bromide by-products and waste of water resources.
By electrolytic preparation method, 1-aminoanthraquinone-2-sulfonic acid is electrolyzed in hydrochloric acid by electrolyzing 1-amino-4-chloranthraquinone-2-sulfonic acid is formed by in situ chlorination, and 1-amino-4-chloranthraquinone-2-sulfonic acid is formed by electrolyzing the electrolytic preparation method, and in the carbonic acid with M acid in the autoclave Condensation reaction was carried out in the presence of sodium hydrogen and copper sulfate to prepare C.I. active blue 49 chromogroup.
The use of stannous chloride is avoided, and the hydrolysis and debrominated by-product of bromide is reduced, and environmental pollution and waste of water resources are reduced.
Smart Images

Figure CN119392271A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fine chemicals, and in particular to a method for preparing a CI reactive blue 49 chromophore by electrolysis. Background Art
[0002] Reactive dyes produced based on CI Reactive Blue 49 color base have the advantages of bright color, good wet fastness, good light fastness and strong applicability. They are widely used in dyeing and printing of cotton, linen, wool and other fibers and their blended fabrics.
[0003] The reaction is an Ullmann condensation reaction of 1-amino-4-bromoanthraquinone-2-sulfonic acid (bromoamic acid) and 1,3,5-trimethyl-2,4-diaminobenzenesulfonic acid (M acid) under the catalysis of copper salt. The process is as follows:
[0004]
[0005] Studies have shown that the reaction is catalyzed by monovalent copper. In industry, stannous chloride is often added to reduce divalent copper to monovalent copper to catalyze the reaction. Since monovalent copper is unstable in water and will disproportionately convert to divalent copper and zero-valent copper and lose its catalytic activity, it is necessary to intermittently add stannous chloride and copper sulfate to maintain the concentration of monovalent copper in the reaction system to allow the reaction to proceed smoothly. However, stannous chloride is toxic and has great environmental hazards. At the same time, the deactivation of the catalyst will also lead to bromoamic acid side reactions, increasing the byproducts of bromoamic acid hydrolysis and debromination:
[0006]
[0007] The presence of these byproducts will affect the color of the finished dye, and a large amount of water is needed to wash them away, resulting in a huge waste of water resources, further increasing the environmental burden. Patent CN116574036A uses organic ligands to stabilize monovalent copper for the preparation of CI Reactive Blue 49 color base, but ascorbic acid and other reducing agents are still added to make the reaction proceed. Therefore, it is very necessary to study and develop a green and efficient preparation method of CI Reactive Blue 49 color base. Summary of the invention
[0008] The purpose of the present invention is to solve the above-mentioned problems of stannous chloride polluting the environment, debromination and hydrolysis of bromoamic acid, and provide a method for preparing CI reactive blue 49 color base by electrolysis, avoiding the use of stannous chloride, and greatly reducing the by-products of hydrolysis and debromination of bromoamic acid, thereby solving the problem of severe environmental pollution of the reaction.
[0009] To achieve the above object, the technical solution of the present invention is as follows: a method for preparing CI reactive blue 49 chromophore by electrolysis, the reaction is as follows:
[0010]
[0011] The method includes the following two steps: (1) (2):
[0012] (1) dissolving 1-aminoanthraquinone-2-sulfonic acid in hydrochloric acid as an electrolyte in the anode chamber, using hydrochloric acid of the same concentration as an electrolyte in the cathode chamber, using constant current electrolysis, and in-situ chlorination in the anode chamber to obtain 1-amino-4-chloroanthraquinone-2-sulfonic acid;
[0013] (2) The 1-amino-4-chloroanthraquinone-2-sulfonic acid obtained in step (1) is condensed with M acid in an autoclave with water as solvent, sodium bicarbonate as base and copper sulfate as catalyst to obtain CI Reactive Blue 49 color base.
[0014] in:
[0015] The mass percentage of the 1-aminoanthraquinone-2-sulfonic acid in the hydrochloric acid is 1% to 15%, preferably 3% to 10%; the concentration of the hydrochloric acid is 10% to 30%, preferably 15% to 25%;
[0016] The electrolysis conditions are:
[0017] The anode is a platinum electrode of different sizes or shapes; the cathode is a graphite electrode of different sizes or shapes; the power supply type is direct current, and the current density is 50~500 mA cm -2 , preferably 100~300 mA cm -2 The electrolytic cell type is an H-shaped electrolytic cell of various sizes or capacities, and the positive and negative chambers are separated by a DuPont proton exchange membrane; the electrolysis temperature is 0~30℃, preferably 10~25℃; the electrolysis time is 3~12 h.
[0018] The molar ratio of 1-amino-4-chloroanthraquinone-2-sulfonic acid to M acid is 1:1.5-1:2.5, the molar ratio of 1-amino-4-chloroanthraquinone-2-sulfonic acid to sodium bicarbonate is 1:3-1:6, the molar ratio of 1-amino-4-chloroanthraquinone-2-sulfonic acid to copper sulfate is 1:005-1:0.2, and the concentration of 1-amino-4-chloroanthraquinone-2-sulfonic acid in the reaction system is 10%-15%.
[0019] The autoclave is a stainless steel reactor that meets national standards and has a gas charging and discharging port. Nitrogen is used to replace the air in the autoclave three times before the reaction.
[0020] The reaction time is 1-4 h, and the reaction temperature is 90-180° C., preferably 100-140° C.
[0021] Compared with the prior art, the present invention achieves the following technical effects:
[0022] In the industrial production of CI Reactive Blue 49 color base, a large amount of stannous chloride or organic reducing agent is required to maintain the concentration of monovalent copper in the catalyst, but heavy metals and high COD in wastewater will cause huge environmental damage, and the generation of bromoamic acid byproducts cannot be fundamentally avoided, which in turn causes the problem of large water consumption. The present invention utilizes electrochemical in-situ chlorination to prepare 1-amino-4-chloroanthraquinone-2-sulfonic acid, and condenses it with M acid in an autoclave without adding a reducing agent to prepare CI Reactive Blue 49 color base. The introduction of stannous chloride and organic reducing agent is avoided, environmental pollution is greatly reduced, bromoamic acid hydrolysis byproducts and debromination byproducts are fundamentally eliminated, and water consumption is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the mass spectrum of 1-aminoanthraquinone-2-sulfonic acid.
[0024] Figure 2 This is the mass spectrum of 1-amino-4-chloroanthraquinone-2-sulfonic acid.
[0025] Figure 3 It is a liquid chromatogram of electrochemical in situ chlorination of 1-aminoanthraquinone-2-sulfonic acid to obtain 1-amino-4-chloroanthraquinone-2-sulfonic acid.
[0026] Figure 4 This is the mass spectrum of CI Reactive Blue 49 chromophore. DETAILED DESCRIPTION
[0027] Example 1
[0028] Take 2.3 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 50 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the same volume and concentration of hydrochloric acid solution. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum mesh electrode was cut into 2×2 cm 2 The graphite felt was ultrasonically cleaned with acetone and ultrapure water, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 150 mAcm -2 The current density was 1.3777 W / m2 and the electrolyte was centrifuged to obtain solids at 30 °C for 7 h. The mass spectrum is shown in Figure 2. Figure 2 As shown, molecular weight 337, m / z 336 [MH] - , 673[2M-H] - .
[0029] Take 1.5 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 1.65 g M acid, 1.7 g sodium bicarbonate, 0.11 g copper sulfate pentahydrate, and then measure 11 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 100°C and turn on magnetic stirring. Keep warm for 3 hours, stop stirring and heating, cool to room temperature, dilute the material with water by 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5~3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 89%. The liquid phase diagram is as follows Figure 3 As shown in the figure, the chromatographic peak at RT = 10.3 min is the target peak.
[0030] Mass spectra such as Figure 4 As shown, molecular weight 531, m / z 530 [MH] - .
[0031] Example 2
[0032] Take 5.5 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 200 mA cm -2 The electrolysis was carried out at 25°C for 6 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0033] Take 3 g of 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.6 g of M acid, 3.3 g of sodium bicarbonate, 0.2 g of copper sulfate pentahydrate, and then add 21 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 110 ° C and start magnetic stirring. Keep warm for 3 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% of the dilution volume of calcium carbonate and 1% of activated carbon, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 91%.
[0034] Example 3
[0035] Take 3.2 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 50 mL of 18% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the same volume and concentration of hydrochloric acid solution. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the electrolysis was carried out at 250 mA cm -2 The electrolysis was carried out at 30°C for 7 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0036] Take 2.1 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.2 g M acid, 2.3 g sodium bicarbonate, 0.15 g copper sulfate pentahydrate, and then add 15 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 180 ° C and start magnetic stirring. Keep warm for 1 hour, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 82%.
[0037] Example 4
[0038] Take 7.4 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode was cut into 2×2 cm 2 The graphite felt was ultrasonically cleaned with acetone and ultrapure water in turn, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 150 mA cm -2 The electrolysis was carried out at 25°C for 8 h at a current density of 1.5 %. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0039] Take 3.4 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.7 g M acid, 3.8 g sodium bicarbonate, 0.24 g copper sulfate pentahydrate, and then add 24 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 150 ° C and start magnetic stirring. Keep warm for 2 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 85%.
[0040] Example 5
[0041] Take 10 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 150 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 100 mA cm -2 The electrolysis was carried out at 30°C for 10 h at a current density of 1.50, and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0042] Take 5.7 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 8.6 g M acid, 6.3 g sodium bicarbonate, 0.4 g copper sulfate pentahydrate, and then add 40 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 110 ° C and start magnetic stirring. Keep warm for 2 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 90%.
[0043] Example 6
[0044] Take 12.5 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 150 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the electrolysis was carried out at 250 mA cm -2 The electrolysis was carried out at 25°C for 10 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0045] Take 6.5 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 8.5 g M acid, 7.2 g sodium bicarbonate, 0.46 g copper sulfate pentahydrate, and then add 46 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 100 ° C and start magnetic stirring. Keep warm for 3 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 89%.
[0046] Example 7
[0047] Take 8.9 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 18% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode was cut into 2×2 cm 2 The graphite felt was ultrasonically cleaned with acetone and ultrapure water in turn, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 220 mA cm -2 The electrolysis was carried out at 30°C for 9 h at a current density of 1.50 g. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0048] Take 4.2 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 5.9 g M acid, 4.7 g sodium bicarbonate, 0.3 g copper sulfate pentahydrate, and then add 30 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 130 ° C and start magnetic stirring. Keep warm for 3 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 83%.
[0049] Example 8
[0050] Take 5.4 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 190 mA cm -2 The electrolysis was carried out at 25°C for 8 h at a current density of 1.5 %. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0051] Take 2.8 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.1 g M acid, 3.1 g sodium bicarbonate, 0.2 g copper sulfate pentahydrate, and then add 20 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 110 ° C and start magnetic stirring. Keep warm for 1 hour, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 88%.
[0052] Example 9
[0053] Take 7.6 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 200 mA cm -2 The electrolysis was carried out at 30°C for 7 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0054] Take 2.7 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.2 g M acid, 3 g sodium bicarbonate, 0.19 g copper sulfate pentahydrate, and then measure 11 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 100°C and start magnetic stirring. Keep warm for 5 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5~3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 87%.
[0055] Example 10
[0056] Take 2.3 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 50 mL of 18% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is a hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum electrode was cut into 2×2 cm 2 The graphite felt was ultrasonically cleaned with acetone and ultrapure water, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 300 mAcm -2 The electrolysis was carried out at 25°C for 8 h at a current density of 1.5 %. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0057] Take 1.3 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 2 g M acid, 1.5 g sodium bicarbonate, 0.09 g copper sulfate pentahydrate, and then add 9 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 130 ° C and start magnetic stirring. Keep warm for 2 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 87%.
[0058] Embodiment 11
[0059] Take 4.7 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 50 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the same volume and concentration of hydrochloric acid solution. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 300 mAcm -2 The electrolysis was carried out at 30°C for 10 h at a current density of 1.50, and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0060] Take 3 g of 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.3 g of M acid, 3.3 g of sodium bicarbonate, 0.2 g of copper sulfate pentahydrate, and then add 20 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 120 ° C and start magnetic stirring. Keep warm for 2 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% of the dilution volume of calcium carbonate and 1% of activated carbon, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 90%.
[0061] Example 12
[0062] Take 6.6 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 300 mA cm -2 The electrolysis was carried out at 25°C for 10 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0063] Take 3.1 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 4 g M acid, 3.5 g sodium bicarbonate, 0.2 g copper sulfate pentahydrate, and then add 22 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 150 ° C and start magnetic stirring. Keep warm for 1 h, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 h, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 83%.
[0064] Embodiment 13
[0065] Take 8 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 150 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is a hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 290 mAcm -2 The electrolysis was carried out at 30°C for 9 h at a current density of 1.50 g. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0066] Take 4.6 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 6.9 g M acid, 5.1 g sodium bicarbonate, 0.33 g copper sulfate pentahydrate, and then measure 33 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 140°C and start magnetic stirring. Keep it warm for 3 hours, stop stirring and heating, cool it to room temperature, dilute the material with water by 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5~3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 81%.
[0067] Embodiment 14
[0068] Take 4.1 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 18% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is a hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode was cut into 2×2 cm 2 The graphite felt was ultrasonically cleaned with acetone and ultrapure water in turn, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 150 mA cm -2 The electrolysis was carried out at 25°C for 5 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0069] Take 1.5 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 1.7 g M acid, 1.7 g sodium bicarbonate, 0.11 g copper sulfate pentahydrate, and then measure 11 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 110°C and start magnetic stirring. Keep warm for 4 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5~3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 82%.
[0070] Embodiment 15
[0071] Take 7.2 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 150 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 200 mA cm -2 The electrolysis was carried out at 30°C for 6 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0072] Take 3.9 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 4.7 g M acid, 4.3 g sodium bicarbonate, 0.28 g copper sulfate pentahydrate, and then measure 28 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 120°C and start magnetic stirring. Keep it warm for 2 hours, stop stirring and heating, cool it to room temperature, dilute the material with water by 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 87%.
[0073] Example 16
[0074] Take 6.1 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 120 mA cm -2 The electrolysis was carried out at 25°C for 7 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0075] Take 2.7 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.5 g M acid, 3 g sodium bicarbonate, 0.19 g copper sulfate pentahydrate, and then measure 19 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 130°C and turn on magnetic stirring. Keep warm for 3 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5~3.0 with hydrochloric acid, stir for 1 hour, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 77%.
[0076] Embodiment 17
[0077] Take 3.5 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the same volume and concentration of hydrochloric acid solution. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 280 mA cm -2 The electrolysis was carried out at 25°C for 4 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0078] Take 1.9 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 2.7 g M acid, 2.1 g sodium bicarbonate, 0.13 g copper sulfate pentahydrate, and then measure 13 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 110 ° C and turn on magnetic stirring. Keep warm for 4 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat it to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 92%.
[0079] Embodiment 18
[0080] Take 5.9 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 18% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is a hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 280 mA cm -2 The electrolysis was carried out at 25°C for 4 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0081] Take 2.4 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.6 g M acid, 2.7 g sodium bicarbonate, 0.17 g copper sulfate pentahydrate, and then measure 17 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 100 ° C and start magnetic stirring. Keep it warm for 3 hours, stop stirring and heating, cool it to room temperature, dilute the material with water 2 times, heat it to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 82%.
[0082] Embodiment 19
[0083] Take 8.8 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 150 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the same volume and concentration of hydrochloric acid solution. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 120 mA cm -2 The electrolysis was carried out at 30°C for 8 h at a current density of 1.5 %. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0084] Take 5 g of 1-amino-4-chloroanthraquinone-2-sulfonic acid, 5.5 g of M acid, 5.6 g of sodium bicarbonate, 0.36 g of copper sulfate pentahydrate, and then measure 35 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 150°C and start magnetic stirring. Keep it warm for 2 hours, stop stirring and heating, cool it to room temperature, dilute the material with water by 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 84%.
[0085] Embodiment 20
[0086] Take 4.2 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode was cut into 2×2 cm 2 The graphite felt was ultrasonically cleaned with acetone and ultrapure water in turn, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 150 mA cm -2 The electrolysis was carried out at 25°C for 6 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0087] Take 2.4 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.6 g M acid, 2.7 g sodium bicarbonate, 0.17 g copper sulfate pentahydrate, and then measure 17 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 140°C and start magnetic stirring. Keep it warm for 2 hours, stop stirring and heating, cool it to room temperature, dilute the material with water by 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 85%.
[0088] Embodiment 21
[0089] Take 10.5 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 150 mL of 18% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 200 mA cm -2 The electrolysis was carried out at 30°C for 8 h at a current density of 1.5 %. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0090] Take 6 g of 1-amino-4-chloroanthraquinone-2-sulfonic acid, 7.2 g of M acid, 6.7 g of sodium bicarbonate, 0.43 g of copper sulfate pentahydrate, and then measure 43 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 100°C and start magnetic stirring. Keep it warm for 3 hours, stop stirring and heating, cool it to room temperature, dilute the material with water by 2 times, heat it to 90°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 89%.
[0091] Embodiment 22
[0092] Take 6.3 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 100 mL of 20% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 180 mA cm -2 The electrolysis was carried out at 25°C for 7 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0093] Take 3.2 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 3.5 g M acid, 3.6 g sodium bicarbonate, 0.23 g copper sulfate pentahydrate, and then add 23 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 120 ° C and start magnetic stirring. Keep warm for 2 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI reactive blue 49 dye color base with a yield of 90%.
[0094] Embodiment 23
[0095] Take 8.7 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 150 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion 117 proton exchange membrane. 2 The platinum electrode was cut into 2×2 cm 2 The graphite felt was ultrasonically cleaned with acetone and ultrapure water in turn, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the flow rate was 300 mA cm -2 The electrolysis was carried out at 30°C for 9 h at a current density of 1.50 g. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0096] Take 4.7 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 6.6 g M acid, 5.2 g sodium bicarbonate, 0.33 g copper sulfate pentahydrate, and then measure 33 mL of water and add it to a stainless steel autoclave. After nitrogen replacement 3 times, heat it to 100°C and start magnetic stirring. Keep it warm for 3 hours, stop stirring and heating, cool it to room temperature, dilute the material with water 2 times, heat it to 110°C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5~3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40°C, and detect it with high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 91%.
[0097] Embodiment 24
[0098] Take 3.4 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 50 mL of 18% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is the same volume and concentration of hydrochloric acid solution. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolytic device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the current was 150 mA cm -2 The electrolysis was carried out at 25°C for 7 h at a current density of , and samples were taken for liquid chromatography analysis. The power was turned off, and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0099] Take 1.6 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 2.1 g M acid, 1.8 g sodium bicarbonate, 0.11 g copper sulfate pentahydrate, and then add 11 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 130 ° C and start magnetic stirring. Keep warm for 2 hours, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 87%.
[0100] Embodiment 25
[0101] Take 2 g of 1-aminoanthraquinone-2-sulfonic acid, add deionized water and hydrochloric acid to prepare 50 mL of 15% hydrochloric acid solution as the electrolyte in the anode chamber, and the electrolyte in the cathode chamber is a hydrochloric acid solution of the same volume and concentration. The anode and cathode chambers are separated by DuPont Nafion117 proton exchange membrane. 2 The platinum mesh electrode and the 0.8 mm diameter graphite rod were ultrasonically cleaned with acetone and ultrapure water in sequence, and then formed into a complete electrolysis device with the electrolytic cell. A magnet was added to the anode chamber, stirring was started, and the electrolysis was carried out at 250 mA cm -2 The electrolysis was carried out at 30°C for 11 h at a current density of 1.5 %. Samples were taken for liquid chromatography analysis. The power was turned off and the electrolyte in the anode chamber was centrifuged to separate the solid, which was 1-amino-4-chloroanthraquinone-2-sulfonic acid after drying.
[0102] Take 1.2 g 1-amino-4-chloroanthraquinone-2-sulfonic acid, 1.3 g M acid, 1.3 g sodium bicarbonate, 0.1 g copper sulfate pentahydrate, and then add 9 mL of water to a stainless steel autoclave. After nitrogen replacement 3 times, heat to 140 ° C and start magnetic stirring. Keep warm for 1 hour, stop stirring and heating, cool to room temperature, dilute the material with water 2 times, heat to 90 ° C, add 2% calcium carbonate and 1% activated carbon by volume of the dilution, and filter to remove impurities. Adjust the pH to 2.5-3.0 with hydrochloric acid, stir for 2 hours, precipitate excess M acid, filter, rinse with water at 40 ° C, and detect by high performance liquid chromatography. It does not contain hydrolysis and dechlorination by-products. The product is CI Reactive Blue 49 dye color base with a yield of 89%.
Claims
1. A method for preparing CI Reactive Blue 49 chromophore by electrolysis, characterized in that: The following steps are involved: ; (1) dissolving 1-aminoanthraquinone-2-sulfonic acid in hydrochloric acid as an electrolyte in the anode chamber, using a hydrochloric acid solution as an electrolyte in the cathode chamber, using a constant current electrolysis, and in-situ chlorination in the anode chamber to obtain 1-amino-4-chloroanthraquinone-2-sulfonic acid; (2) The 1-amino-4-chloroanthraquinone-2-sulfonic acid obtained in step (1) is condensed with 1,3,5-trimethyl-2,4-diaminobenzenesulfonic acid in an autoclave with water as solvent, sodium bicarbonate as base and copper sulfate as catalyst to obtain CI Reactive Blue 49 color base.
2. A method for preparing CI Reactive Blue 49 color base by electrolysis according to claim 1, characterized in that: The mass percentage of the 1-aminoanthraquinone-2-sulfonic acid in the hydrochloric acid is 1% to 15%, and the concentration of the hydrochloric acid is 10% to 30%.
3. A method for preparing CI Reactive Blue 49 color base by electrolysis according to claim 1, characterized in that: The anode of the electrolysis is a platinum electrode; the cathode is a graphite electrode; the power supply type is direct current, and the current density is 50~500 mA cm -2 The electrolytic cell type is an H-shaped electrolytic cell, and the positive and negative chambers are separated by a proton exchange membrane; the electrolysis temperature is 0~30℃; the electrolysis time is 3~12 h.
4. The method for preparing CI Reactive Blue 49 color base by electrolysis according to claim 1, characterized in that: The molar ratio of 1-amino-4-chloroanthraquinone-2-sulfonic acid to 1,3,5-trimethyl-2,4-diaminobenzenesulfonic acid is 1:1.5-1:2.5, the molar ratio of 1-amino-4-chloroanthraquinone-2-sulfonic acid to sodium bicarbonate is 1:3-1:6, the molar ratio of 1-amino-4-chloroanthraquinone-2-sulfonic acid to copper sulfate is 1:0.05-1:0.2, and the mass percentage of 1-amino-4-chloroanthraquinone-2-sulfonic acid in the reaction system is 10%-20%.
5. The method for preparing CI Reactive Blue 49 color base by electrolysis according to claim 1, characterized in that: The pressure autoclave is a stainless steel reactor with gas charging and discharging ports, and nitrogen is used to replace the air in the autoclave before the reaction.
6. The method for preparing CI Reactive Blue 49 color base by electrolysis according to claim 1, characterized in that: The condensation time is 1-4 h, and the reaction temperature is 90-180°C.
Citation Information
Patent Citations
Preparation method of C.I. Reactive blue 49 color base
CN116574036A
Electrochemical preparation method of bromamine acid amination product
CN117888124A
Process for preparing aniline derivatives
EP0313160A1
Method for the electrochemical reduction of vat and sulphur dyes
EP1563137A1